Contrasting effect of irrigation practices on the cotton rhizosphere microbiota and soil functionality in fields - Peng, Bin; Zhao, Shuai; Banerjee, Samiran; Mai, Wenxuan; Tian, Changyan (Frontiers in Plant Science, 2022)
Drip irrigation under plastic film mulch is a common agricultural practice used to conserve water. However, compared to traditional flood irrigation with film mulch, this practice limit cotton root development from early flowering stage and may cause premature senescence in cotton. Changes of root will consequently shape the composition and activity of rhizosphere microbial communities, however, the effect of this farming practice on cotton rhizosphere microbiota remains poorly understood. This study investigated rhizosphere bacteria and soil functionality in response to different irrigation practices —including how changes in rhizosphere bacterial diversity alter soil nutrient cycling. Drip irrigation under plastic film mulch was shown to enhance bacterial diversity by lowering the salinity and increasing the soil moisture. However, the reduced root biomass and soluble sugar content of roots decreased potential copiotrophic taxa, such as Bacteroidetes, Firmicutes, and Gamma-proteobacteria, and increased potential oligotrophic taxa, such as Actinobacteria, Acidobacteria, and Armatimonadetes. A core network module was able to determine the functional potential of the soil. This module not only contained most of the keystone taxa but also comprised taxa belonging to Planctomycetaceae, Gemmatimonadaceae, Nitrosomonadaceae, and Rhodospirillaceae that were positively associated with functional genes involved in nutrient cycling. Drip irrigation signiﬁcantly decreased the richness of the core module and reduced the functional potential of soil in the rhizosphere. Overall, this study provides evidence that drip irrigation under plastic film mulch alters the core bacterial network module and suppresses soil nutrient cycling.